(untitled) (Applied Biological Research, 2016)
Investigations were undertaken to assess the effects of mulching, bio inoculants and inorganic chemicals on shelf-life of mango cv. Alphonso.Anthracnose Pre-harvest sprays with bio-inoculant (Pseudomonas fluorescens FP7 along with chitin) were sprayed six times at 15 days interval starting from 15 days before expected flowering time of mango trees. Calcium chloride (2, 4 and 6%), calcium nitrate (4%), potassium sulphate (1%) and borax (1%) were sprayed 30 days prior to harvest. Highest tree height, tree girth and tree spread were observed when mulching with mango dried leaves was done along with spraying of Pseudomonas fluorescens FP7 (0.2%) with chitin (0.5%) and 1% CaCl2. At post harvest stage the same treatment exhibited delayed ripening, lowest physiological loss in weight, reduced anthracnose infection, increased duration for degreening and resulted in extended shelf- life. It also registered the highest TSS, reducing sugars, non-reducing and total sugars, lowest titrable acidity, ascorbic acid content at the end of storage period of 15.20 days.